Muslim friendly attributes as a new attraction in tourism accommodation premises industry - Othman, Rashidi (Yamani Angle Sdn Bhd, 2021)
The recent tourism trends increase the demand for Islamic hospitality services. Shariah-compliant health and wellness are new innovative and inventive facilities originate in the hotel trade. This development can be found in countries where muslim occupant is the majority population. It associated with the earlier study that from Muslim clients is one the very significant for the target marketplace of Shariah health and wellness principle. Shariah compliant hotel can be defined as a hotel that provides services based on Shariah law. In order to be known as Shariah-compliant hotel (SCH), the hoteliers must follow the entire requirement given according to Shariah. The SCH is not limited to serve halal food and drinks onlu but the whole operation of the hotel also in accordance with Shariah principles. Hence, this research aimed to explore the implementation of Shariah-compliant hotels (SCH) in Malaysia. It is much recommended to promote aggressively about SCH in order to stimulate and get a positive impact on the tourism industry.